Design technology of mosque mimbar Kedah Darulaman / Ahmad Faisol Yusof, Mohamad Zaki Yusof and Jamaludin Muhamad - Yusof, Ahmad Faisol; Yusof, Mohamad Zaki; Muhamad, Jamaludin (Research Management Institute (RMI), 2011)
Every muslim know that mosque is place for them to pray and praise to Allah S.W.T. Mosque become important place for muslim together to do an activity such as learning centre, war strategy and so on. At the same time mosque is for muslim to learn about life in this world and after death (akhirat). Muslim also learns at mosque about Islamic law which is knowledge likes muamalah (business) matter, people relationship among muslim with muslim or muslim with non-muslim.